The derivation of effects threshold concentrations of lead for European freshwater ecosystems. (24th February 2016) - Van Sprang, Patrick A.; Nys, Charlotte; Blust, Ronny J.P.; Chowdhury, Jasim; Gustafsson, Jon P.; Janssen, Colin J.; De Schamphelaere, Karel A.C.
Abstract: The main objective of the present study was to derive ecologically relevant effect threshold concentrations of (dissolved) Pb for selected European Union (EU) freshwater rivers, using the 2008 EU Voluntary Risk Assessment Report as a starting point and more advanced methodologies than those used in the Voluntary Risk Assessment Report. This included 1) implementing more robust quality criteria for selecting chronic toxicity data; 2) the conversion of total to dissolved Pb concentrations using a combination of an empirical equation relating inorganic Pb solubility and geochemical speciation modeling to account for effects of dissolved organic matter; 3) the use of bioavailability models for chronic toxicity for species belonging to 3 different trophic levels; and 4) the use of robust methods for large data set handling (such as species sensitivity distribution [SSD] analysis). The authors used published bioavailability models for an algal species ( Pseudokirchneriella subcapitata ) and a daphnid ( Ceriodaphnia dubia ) and developed a new model for the fathead minnow ( Pimephales promelas ). The research has shown that these models are also useful for, and reasonably accurate in, predicting chronic toxicity to other species, including a snail, a rotifer, midge larvae, and an aquatic plant (read‐across). A comprehensive chronic toxicity data set for Pb was compiled, comprising 159 individual high‐quality toxicity data for 25 different species. By applying the total dissolved conversion and the bioavailability models, normalized toxicity values were obtained, which were then entered into a SSD analysis. Based on the parametric best‐fitting SSDs, the authors calculated that ecological threshold concentrations of Pb protecting 95% of freshwater species for 7 selected European freshwater scenarios were between 6.3 μg dissolved Pb/L and 31.1 μg dissolved Pb/L. Environ Toxicol Chem 2016;35:1310–1320. © 2015 SETAC